L’empire du soleil couchant - Gaudin, Guillaume (Casa de Velázquez, 2025)
Located in the far west of the Spanish Empire, the Philippines are a perfect testing ground for understanding the role of distance and communications in the functioning of the Hispanic Monarchy. A detailed study of the documentation reveals a wide variety of actors and means used to maintain, and sometimes break, contact between Manila, Mexico City and Madrid. Soldiers, clerics and magistrates, all more or less involved in the Manila Galleon trade, testify, write letters and draft reports according to a precise timetable. They often felt the need to travel between the capitals and the confines, either along the great imperial axes of the carreras and caminos reales, or along interloped routes from the South China Sea to the Mediterranean. The whole is not a system, but an ensemble subject to uncertainty and the need to constantly adapt to the vagaries of distance.